(untitled) (Journal of Naval Architecture and Marine Engineering, 2018)
An analysis of the thermal radiation and viscous dissipation effects on an unsteady MHD mixed convection flow of a viscous incompressible fluid past a vertical porous plate, in the presence of variable wall heat flux and heat generation/absorption is presented. The free stream velocity follows an exponentially increasing or decreasing small perturbation law. The governing equations of the flow field are transformed into a system of non-linear ordinary differential equations by perturbation technique and then solved numerically by using the shooting method. The effects of the various parameters on the translation velocity, microrotation and temperature as well as the skin friction coefficient and couple stress coefficient at the wall are prepared with various values of the fluid properties.